Acute fulminant necrotizing amebic colitis in a pediatric patient: a rare complication of amebiasis with high mortality-a case report - Samantha Kiriwaththuduwa; Romola Gnanapragasam; Anjalie Amarasinghe; Yugantha Adikari; Shanika Ranasinghe; Rumala Morel; Chanuka Dharmaratne; Lakmalee Bandara (SpringerOpen, 2020)
Abstract Background The majority of amebic infections among humans remain asymptomatic. Rarely, the disease takes a fulminant acute course due to the development of necrotizing amebic colitis. This complication is usually found in adult patients. However, on the contrary, this case was diagnosed in a 9-year-old patient. He was transferred to the Sirimavo Bandaranayake Specialized Children's Hospital (SBSCH), Peradeniya from the District General Hospital, Kilinochchi. To our knowledge, this is the first report of this rare complication in a child in Sri Lanka. Case presentation We present a case of acute fulminant necrotizing amebic colitis in a 9-year-old boy. Surgical exploration revealed extensive ulceration and multiple perforations in the entire colon. PAS-Martius Yellow 40 stain highlighted amebae with erythrophagocytosis within the necrotic debris of the ulcers. The polymerase chain reaction (PCR) that was conducted to confirm the diagnosis was positive for Entameba histolytica. The post-operative course was marked with antimicrobial treatment for septicemia and the need for ventilator assistance. Antimicrobial treatment included intravenous metronidazole. The patient progressively recovered and was discharged on a normal diet. Conclusion This case reports an acute fulminant necrotizing amebic colitis in a 9-year-old patient. After the treatments, the patient progressively recovered and was discharged on a normal diet. E. histolytica infections in northern Sri Lanka should be given attention as a public health concern. Furthermore, this case highlights that acute fulminant amebic colitis requires early surgical intervention, aggressive supportive and anti-amebic treatments. Clinicians should be cognizant of this potentially fatal complication of amebic colitis.